(untitled) (Fiep Bulletin - online, 2014)
This field research main objective was to characterize the psychomotor profile of fifth grade scholars in fundamental teaching of Caxias do Sul City (Rio Grande do Sul, Brazil), aiming to analyze similarities and differences in relation to seven psychomotor performance metrics: tonicity, equilibration, lateralization, body notion, space-time structure, global praxis and fine praxis. Besides, it had the purpose of evaluate the validity of physical education classes with and without specialized teacher, because the initial grades of physical education classes in public schools is not performed by a specialized teacher. The study was accomplished with 846 children between 10 and 14 years old enrolled during 2006, representing about 10% of the county age group. To support the data acquisition we used an agreement term, a questionnaire and the Fonseca´s Psychomotor Battery (FONSECA, 1995). The results concluded that there is not a dominant profile in the seven analyzed metrics, neither significant difference between teaching systems (public or private), children sex (male of female) and beginning year of physical education classes (initial grades or fifth grade). The study also concluded that the psychomotor development level is very low in the researched city, and the scholar physical education needs a reevaluation and reformulated, as the main classes goals are not being reached.